Simulation of the seismic-stability problem for buried constructions - Dyukina, N. S.; Bazhenov, V. G. (Journal of machinery manufacture and reliability, 2015)
A procedure for the numerical simulation of seismic effects on a buried construction on a transversely isotropic multilayer base is proposed subject to the effects of contact interactions and the gravity field with an accelerogram at the day surface. The effects of the location of the earthquake hypocenter on the horizontal and vertical displacements of construction walls and the adjacent ground are estimated. The great significance of the consideration of the mechanical characteristics of the ground depending on the depth and the gravity field is shown for loose bases.